EVALUASI STRUKTUR GEDUNG FAKULTAS HUKUM UNIVERSITAS ISLAM INDONESIA YOGYAKARTA BERDASARKAN PERCEPATAN GEMPA YANG DIHITUNG SECARA PROBABILISTIK - Wisnu Erlangga; Lalu Makrup; Malik Musthofa; Suharyatmo (TEKNISIA, 2022)
Earthquake shocks generally cause the biggest shocks in building structures. Earthquake waves, generated by an earthquake event, are the main cause of this shaking. A new building of the Faculty of Law, Islamic University of Indonesia, was selected for this research to evaluate the effect of earthquake shaking on the structural response. A developed time history-based artificial earthquake ground motion was used in the structural analysis. Furthermore, the time history was developed based on spectral matching with target spectra derived from a probabilistic seismic hazard analysis. This analysis results in the building structure's seismic response, which is then evaluated based on the parameters set by the earthquake standards/regulations for buildings. This building is relatively safe against design earthquake shocks based on the results.